2000
DOI: 10.1603/0022-0493-93.3.584
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Integrating Eleven Agricultural Insecticides with the Predatory Bug <I>Pristhesancus plagipennis</I> (Hemiptera: Reduviidae)

Abstract: A problem for growers attempting to implement integrated pest management programs is the lack of information regarding the compatibility of insecticides with natural enemies. To provide information about this problem, we evaluated the acute and residual effects of 11 commonly used insecticides on nymphs of Pristhesancus plagipennis (Walker) under both laboratory and field conditions. For each insecticide, the length of time that weathering residues caused > 50% mortality was evaluated and compared against the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…Previous registered options for Creontiades spp. control were predominantly organophosphate products, such as dimethoate and omethoate, which were found to be highly toxic to P. plagipennis during this and earlier experiments (Grundy et al , 2000a). The high toxicity of diafenthiuron to P. plagipennis was unexpected as previous research on related predators such as Nabis , Geocoris and Orius spp.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Previous registered options for Creontiades spp. control were predominantly organophosphate products, such as dimethoate and omethoate, which were found to be highly toxic to P. plagipennis during this and earlier experiments (Grundy et al , 2000a). The high toxicity of diafenthiuron to P. plagipennis was unexpected as previous research on related predators such as Nabis , Geocoris and Orius spp.…”
Section: Discussionsupporting
confidence: 64%
“…Four-day-old first instar P. plagipennis were used in each experiment, as earlier studies indicated that this stage was the most sensitive and, therefore, provided a ‘worst case’ test result (Grundy et al , 2000a). Pesticides that are found to be non-toxic using the assumptions of a ‘worst case’ test generally require no further testing on other stages (Hassan et al , 1994).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the target pests, broad-spectrum pesticides (that kill insects and mites indiscriminately) may affect non-target invertebrate species ( Readshaw, 1975 ), including causing reductions in natural enemy population abundance and activity (e.g., Wilson, Bauer & Lally, 1998 ; Wilson, Bauer & Lally, 1999 ), and competition between pest species (known as competitive release, Zeilinger, Olson & Andow, 2016 ). Assays of invertebrates against weathered residues have shown the persistence of pesticides might play an important part in their negative impacts on natural enemies in the field ( Grundy et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies (Grundy et al . ; Grundy & Maelzer ; Grundy & Maelzer ; Grundy , ) have assessed the potential of artificially reared P. plagipennis in inundative releases for biocontrol in broad‐acre crops. In cotton and sunflower, where poor nymph dispersal is likely, the mechanical release of nymphs with vermiculite may be possible but requires further testing (Grundy & Maelzer ).…”
Section: Resultsmentioning
confidence: 99%